Jedność między ludźmi w świetle opowiadania o wieży Babel - Basiuk, Maciej (Śląskie Studia Historyczno-Teologiczne, 2011)
In creating people God wanted them to live in a community. For this reason they possessed ability to make relationships with each other. Although through their sins they diminished this ability and destroyed the harmony in the world they had lived. In His mercy God tried to lead people to the primary ideal in various ways, what we can see in the biblical prehistory. But the situation of the Babel’s builders seems to be an opposite act. The story might suggest that Creator destroyed unity of people by confusion of languages. However, detailed analysis of this biblical text shows what is the true message resulted from this story and what is its place in the teaching of the Holy Scripture.